(Pada PT.Gunung Agung Cabang mall Citra Land, Simpang Lima Semarang) - Silalahi, Frisca Aulia; Magnadi, Rizal Hari (Diponegoro Journal of Management, 2016)
This Study  aims to examine the effect of trust, commitment, satisfaction, loyalty, reliability salesperson to the quality of relationships at PT Gunung Agung Branch of Citra  Land mall, Simpang Lima, Semarang. This study uses a trust, commitment, satisfaction, loyalty, reliability salespeople as independent variables and quality of relationships as the dependent variable. This study uses qualitative data analysis with data collection methods using interviews and quantitative is questionnaires. The study involved five employees who are close to the supplier as respondent questionnaires  and  interviews  and  some  suppliers  in  an  interview.  Based  on  the  results  of qualitative  research,  the  reliability  of  salespeople  do  not  affect  the  quality  of  relationships GUNUNG AGUNG PT Citra Land Branch mall, Simpang Lima, Semarang